Automatic generation of landslide profile for complementing landslide inventory. Issue 1 (1st January 2020) - Li, Langping; Lan, Hengxing; Strom, Alexander
Abstract: Landslide profile has been widely used in the dynamics analysis, characteristics illustration and parameter measurement along the longitudinal direction of landslide. However, landslide profile and landslide characteristic parameters that can be derived from landslide profile have not been formally included in landslide inventories. This paper firstly presented a newly developed algorithm for automatic generation of landslide profile, and then suggested 14 parameters that can be directly derived from landslide profile to characterize landslides. The proposed approach has been coded in a freely available R script called ALPA. A case study showed that the profiles of landslides with various scales and morphologies can be successfully generated by ALPA. A correlation analysis suggested that the 14 parameters can provide independent and informative complements to landslide characterization, which are different from the landslide area and volume. The results also implied that landslide area, which quantifies the total area affected by a landslide, is highly correlated with the product of volume and maximum drop height and the product of volume and maximum residual height, which are related to destructive power. Although limited by some complications, ALPA provides a practical tool for producing landslide profiles and landslide characteristic parameters, which are valuable complements to landslide inventory.